Efficient separation of l-phosphinothricin from enzymatic reaction solution using cation-exchange resin. Issue 4 (3rd March 2020) - Lv, Sheng-Zhi; Guo, Yu-Xing; Xue, Ya-Ping; Xu, Jian-Miao; Zheng, Yu-Guo
ABSTRACT: The separation of l -phosphinothricin from reaction solution using cation-exchange resin was investigated. The adsorption and desorption capacities of seven different resins were first tested, and resin 001 × 7 was selected as the suitable resin. The equilibrium adsorption data followed the Freundlich isotherm model, and the adsorption kinetic data fitted with pseudo-second-order equation well. The effect of solution pH on the adsorption and the breakthrough/desorption curves of resin 001 × 7 was studied. The results indicated that under the optimized separation conditions (solution pH value 2.0, feed rate, 1.0 BV h −1, and desorption flow rate 0.5 BV h −1 ), the recovery ratio of l -phosphinothricin from reaction solution reached 98%.